The effect of patient warming on perioperative cardiovascular outcomes in interventional clinical trials: A systematic review and meta-analysis - Mkhize, Sisalindele (Department of Anaesthesia and Perioperative Medicine, 2024)
BACKGROUND: Perioperative cardiovascular events are a common contributor to perioperative morbidity and mortality. Patient warming affects the cardiovascular system in various ways and may protect against cardiovascular events. We aimed to estimate the effect of active patient warming on perioperative cardiovascular outcomes in clinical trials. METHODS: A systematic review with meta-analyses was conducted. Six data bases were searched from inception until 5th July 2021 for studies that prospectively assigned participants to any physical warming strategy and reported on cardiovascular outcomes. Screening, data extraction and risk of bias assessment were conducted in duplicate. 8782 records were identified. After removing duplicates and screening titles and abstracts, fifty-two full-text articles were assessed for eligibility, fourteen studies with 1711 participants were included in the systematic review and meta-analyses. RESULTS: The effect of physical warming was – risk ratio (95% confidence interval from random effects model) - 0.74 (0.11; 4.73) for major adverse cardiovascular events, 1.07 (0.09; 13.03) for myocardial infarction, 0.56 (0.17; 1.85) for myocardial ischaemia, 0.48 (0.19; 1.20) for arrhythmias and 0.77 (0.25; 2.37) for all-cause mortality. Statistical heterogeneity was not concerning in any of the meta-analyses. All of the meta-analyses carried serious risk of bias and represent low quality evidence. CONCLUSION: We found little information on the treatment effect of active patient warming on cardiovascular outcomes. Inconsistent definitions and reporting of cardiovascular events in patient warming trials confound synthesis of the data. We recommend that prospective studies of patient warming routinely report on cardiovascular outcomes. The effect of active patient warming on perioperative cardiovascular outcomes remains an important unanswered question in perioperative medicine.